ANALISIS BEBAN KERJA REKAM MEDIS BERDASARKAN METODE WORKLOAD INDICATOR STAFF NEED (WISN) DI RSUD SUNGAI LILIN - Dewi Nashrulloh; Lely Meriaya sari; Devi Asmayawati (LPPM STIKes Mitra Adiguna, 2024)
The WISN (Workload Indicator Staff Need) method is an indicator that shows the amount of staff needed in health facilities based on workload, so that the allocation/relocation is easier and more rational. Services in hospitals are administrative in nature, namely service that is orderly, neat and thorough. In addition, because other people are facing it, efforts must be made to be fast and not create queues, so a sufficient number of officers or health workers is needed. to calculate the medical record workforce at Sungai Lilin Hospital. This research uses quantitative research with a descriptive approach. The data collection method in this study was observation, direct interviews with officers at Sungai Lilin Hospital. it is known that the available working time is 2,088 hours/year or 125,280 minutes/year, the workload requirement for medical record officers in the medical record room is 642,959 minutes, the calculation of the standard time allowance is 0.15 minutes. The calculation of the medical record workforce in the medical record room is 4 workers. 3 people are already in the medical record room. So we need 1 more worker.